Intravesical prostatic protrusion and prostate volume in patients with acute urine retention - Galeti, Ershad Hussain; Rasool, Mustaq; Bharali, Mriganka Deuri (International Surgery Journal, 2022)
Background: To study the prevalence of significant Intravesical Prostatic Protrusion (IPP) in patients presenting with acute urinary retention (AUR) due to Benign prostatic hyperplasia (BPH) and to study the correlation between intravesical prostatic protrusion and prostatic volume. Methods: We assessed 68 men between the ages 45 to 85 who presented with acute urinary retention. Initial assessment included detailed clinical history, International Prostate Symptom Score (IPSS) and Quality of Life assessments and a transabdominal ultrasonogram to measure Prostate Volume (PV) and Intravesical Prostatic Protrusion (IPP). The degree of IPP was determined by the distance from the tip of the protrusion to the circumference of the bladder at the base of the prostate gland. Patients with IPP >10 mm were taken have significant IPP and those ≤10 mm was taken to be insignificant. Statistical analysis included descriptive analysis and Pearson’s correlation coefficient. Results: Of the 68 patients in our study with resented with AUR, 29 patients (42.9%) had significant IPP. Mean IPP was 9.81mm with a standard deviation of 5.41 mm. All patients with significant IPP had a severe IPPS grade. IPP had a statistically significant correlation with prostatic volume. Conclusions: The IPP as assessed by transabdominal ultrasound can be used to direct appropriate patients to more aggressive treatment strategies like surgery.